Cost‐effectiveness of early cancer surveillance for patients with Li–Fraumeni syndrome. Issue 5 (4th February 2019) - Tak, Casey R.; Biltaji, Eman; Kohlmann, Wendy; Maese, Luke; Hainaut, Pierre; Villani, Anita; Malkin, David; Sherwin, Catherine M.T.; Brixner, Diana I; Schiffman, Joshua D.
Abstract: Introduction: Patients with germline TP53 pathogenic variants (Li–Fraumeni syndrome [LFS]) are at extremely high lifetime risk of developing cancer. Recent data suggest that tumor surveillance for patients with LFS may improve survival through early cancer detection. The objective of this study was to assess the cost‐effectiveness of a cancer surveillance strategy for patients with LFS compared with those whose tumors present clinically. Methods: A Markov decision analytic model was developed from a third‐party payer perspective to estimate cost‐effectiveness of routine cancer surveillance over a patient's lifetime. The model consisted of four possible health states: no cancer, cancer, post‐cancer survivorship, and death. Model outcomes were costs (2015 United States Dollars [USD]), effectiveness (life years [LY] gained), and incremental cost‐effectiveness ratio (ICER; change in cost/LY gained). One‐way sensitivity analyses and probabilistic sensitivity analyses examined parameter uncertainty. Results: The model showed a mean cost of $46 496 and $117 102 and yielded 23 and 27 LY for the nonsurveillance and surveillance strategies, respectively. The ICER for early cancer surveillance versus no surveillance was $17 125 per additional LY gained. At the commonly accepted willingness to pay threshold of $100 000/life‐year gained, surveillance had a 98% probability of being the most cost‐effective strategy for early cancer detection in this high‐risk population. Conclusions: Presymptomatic cancer surveillance is cost‐effective for patients with germline pathogenic variants in TP53 . Lack of insurance coverage or reimbursement in this population may have significant consequences and leads to undetected cancers presenting in later stages of disease with worse clinical outcomes.